Microbial nitrogen limitation in the mammalian large intestine. (December 2018) - Reese, Aspen; Pereira, Fátima; Schintlmeister, Arno; Berry, David; Wagner, Michael; Hale, Laura; Wu, Anchi; Jiang, Sharon; Durand, Heather; Zhou, Xiyou; Premont, Richard; Diehl, Anna; et al.
Abstract Resource limitation is a fundamental factor governing the composition and function of ecological communities. However, the role of resource supply in structuring the intestinal microbiome has not been established and represents a challenge for mammals that rely on microbial symbionts for digestion: too little supply might starve the microbiome while too much might starve the host. We present evidence that microbiota occupy a habitat that is limited in total nitrogen supply within the large intestines of 30 mammal species. Lowering dietary protein levels in mice reduced their faecal concentrations of bacteria. A gradient of stoichiometry along the length of the gut was consistent with the hypothesis that intestinal nitrogen limitation results from host absorption of dietary nutrients. Nitrogen availability is also likely to be shaped by host–microbe interactions: levels of host-secreted nitrogen were altered in germ-free mice and when bacterial loads were reduced via experimental antibiotic treatment. Single-cell spectrometry revealed that members of the phylum Bacteroidetes consumed nitrogen in the large intestine more readily than other commensal taxa did. Our findings support a model where nitrogen limitation arises from preferential host use of dietary nutrients. We speculate that this resource limitation could enable hosts to regulate microbial communities in the large intestine. Commensal microbiota may have adapted to nitrogen-limited settings, suggesting one reason why excess dietary protein has been associated with degraded gut-microbial ecosystems. Faecal carbon:nitrogen measurements and manipulation of nitrogen availability via diet and host secretions in a murine model suggest that intestinal nitrogen limitation occurs due to host absorption and microbial use, leading to benefits for specific taxa.